Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPS Melalui Media Gambar - Noviyanti, Dwi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Learning is a process marked by a change in a person. A teacher must be skilled in determining appropriate strategies, methods, and learning media. Lack of media and teaching aids, students find it difficult to get grades that are in accordance with the KKM. This study aims to determine the improvement of student learning outcomes in social studies subjects using image media in class V SD Negeri Kedungsono 3 is classroom action research. Data collection techniques using the method of observation, documentation and tests. The instruments used in this study were observation sheets for improving student achievement both individually and in groups, student learning independence sheets and evaluation questions. The results of this study were 33.33% in the pre-cycle, 60% in the second cycle, 100% in the third cycle. Based on the results of the research obtained, it is concluded that through the media images can increase the activity and learning outcomes of fifth grade students at SD Negeri Kedungsono 3, Bulu District, Sukoharjo Regency.